1998
DOI: 10.1029/1998je900008
|View full text |Cite
|
Sign up to set email alerts
|

Alteration processes in volcanic soils and identification of exobiologically important weathering products on Mars using remote sensing

Abstract: Abstract. Determining the mineralogy of the Martian surface material provides information about the past and present environments on Mars which are an integral aspect of whether or not Mars was suitable for the origin of life. Mineral identification on Mars will most likely be achieved through visible-infrared remote sensing in combination with other analyses on landed missions. Therefore, understanding the visible and infrared spectral properties of terrestrial samples formed via processes similar to those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 69 publications
2
34
0
2
Order By: Relevance
“…These gossans include poorly-crystalline or nanophase iron oxide and silicate phases as well as jarosite. Morris et al (1996Morris et al ( , 2000 and Bishop et al (1998a) have found jarosite, alunite, alunogen and other sulfate species in a range of volcanic tephra and ash samples formed through hydrothermal alteration. Such Fe-and Al-bearing sulfates also may have formed on Mars through similar processes.…”
Section: Recent Analyses By the Mars Exploration Rovers (Mers) At Thementioning
confidence: 99%
“…These gossans include poorly-crystalline or nanophase iron oxide and silicate phases as well as jarosite. Morris et al (1996Morris et al ( , 2000 and Bishop et al (1998a) have found jarosite, alunite, alunogen and other sulfate species in a range of volcanic tephra and ash samples formed through hydrothermal alteration. Such Fe-and Al-bearing sulfates also may have formed on Mars through similar processes.…”
Section: Recent Analyses By the Mars Exploration Rovers (Mers) At Thementioning
confidence: 99%
“…As the identification method is geared to comparison after continuum removal of absorption features, spectra with extremely weak features were taken to represent unidentifiable Fe minerals or poorly crystallized Fe substances if no match was found. Identification of poorly crystallized nanocrystalline (grain size b9 Am) Fe 3+ minerals, which may be common as pigmentary agents in rocks in the waste piles, is difficult because of the lack of knowledge of their spectral features in natural mixtures, such as those containing well-crystallized Fe minerals (Morris et al, 1993;Bishop et al, 1998). Sulfides, the ultimate target of most aciddrainage remediation, generally can be readily identified in the field through visual examination.…”
Section: Interpretation Of Reflectance Spectramentioning
confidence: 99%
“…One example of such a process is palagonitization of basaltic glass (Morris et al , 1993(Morris et al , 2000, which can yield both nanophase (amorphous) and fine-grained (crystalline) red hematite. In addition to palagonitic alteration, pedogenic and solfataric alteration of basaltic glasses are all capable of producing nanophase and/or fine-grained red hematite (e.g., Bishop et al 1998Bishop et al , 2002Bishop et al , 2004Morris et al , 1993Morris et al , 2000Schiffman et al 2000Schiffman et al , 2002. The preferred formation mechanism proposed by Christensen et al (2000) for the coarse, gray hematite is precipitation from Fe-rich water (at ambient or hydrothermal temperatures).…”
Section: Introductionmentioning
confidence: 99%